ANALISIS DESKRIPTIF PEMASARAN JASA DI STMIK MARDIRA INDONESIA BANDUNG - Ali Mulyawan; Iwan Sidharta (Jurnal Computech & Bisnis (e-Journal), 2015)
Services closely related to the quality of the services provided to customers, as well as with the quality of service received by customers in obtaining the services provided by the college. This study was conducted to investigate the implementation of marketing services performed by using descriptive analysis of the sample of students who meet the established criteria. The results showed that the implementation of the mix of services performed is sufficient that responsiveness aspect is an element of service with the highest scores  and tangible aspects are elements of service with the lowest score.Keywords: marketing services; descriptive analysis; college